EMOTIONAL EXHAUSTION SCALE FOR UNIVERSITY STUDENT: PSYCHOMETRIC PROPERTIES IN A MEXICAN SAMPLE - González Ramírez, Mónica Teresa; Landero Hernández, René (Anales de Psicología / Annals of Psychology, 2007)
Considering the necessity to continue with the research about burnout in university students, it is important to have questionnaires with enough validity and reliability to measure emotional exhaustion, because in students, emotional exhaustion is the way in which burnout is showed. The aim of the study was to confirm the one-factor structure of the Emo-tional Exhaustion Scale in a Mexican students sample, and also, to meas-ure its association with stress, self-esteem and anxiety, and then to have information about its validity in comparison with other variables. The study was made with 506 psychology students of two universities of the North of Mexico, explanatory and confirmatory factorial analysis were used. The results confirm the one-factor structure of the scale, an ade-quate reliability and correlations with stress, anxiety and self-esteem.